2017
DOI: 10.1038/ncomms15565
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast terahertz snapshots of excitonic Rydberg states and electronic coherence in an organometal halide perovskite

Abstract: How photoexcitations evolve into Coulomb-bound electron and hole pairs, called excitons, and unbound charge carriers is a key cross-cutting issue in photovoltaics and optoelectronics. Until now, the initial quantum dynamics following photoexcitation remains elusive in the hybrid perovskite system. Here we reveal excitonic Rydberg states with distinct formation pathways by observing the multiple resonant, internal quantum transitions using ultrafast terahertz quasi-particle transport. Nonequilibrium emergent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
68
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 36 publications
(68 reference statements)
3
68
1
Order By: Relevance
“…[12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence. [26,40] The photophysics of MAPbX 3 nanocrystals have been extensively studied, [41][42][43][44][45][46][47][48][49][50] and there are several reports on various luminescence properties of CsPbX 3 . [19,22,[36][37][38][39] In addition, triple-cation (Cs,formamidinium,methylammonium)PbX 3 materials have been developed with the goal of increasing stability while maintaining bright luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…[12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence. [26,40] The photophysics of MAPbX 3 nanocrystals have been extensively studied, [41][42][43][44][45][46][47][48][49][50] and there are several reports on various luminescence properties of CsPbX 3 . [19,22,[36][37][38][39] In addition, triple-cation (Cs,formamidinium,methylammonium)PbX 3 materials have been developed with the goal of increasing stability while maintaining bright luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…Hence the binding energies of interlayer excitons, which depend sensitively on the delocalization of the electronic wavefunctions over the heterostructure 23 , have not been measured.Signatures of the ultrafast interlayer charge transfer have been studied by interband spectroscopy 8,21 .These techniques, however, cannot measure Coulomb correlations or the formation of interlayer excitons, on the intrinsic ultrashort timescales.Meanwhile, phase-locked electromagnetic pulses in the terahertz (THz) and mid-infrared (MIR) range have directly accessed ultrafast low-energy excitations, such as plasmons, phonons, or correlationinduced energy gaps [25][26][27][28] . By probing the internal 1s-2p resonance, pre-existing exciton populations have been studied, even if interband selection rules render them optically dark 19,20,26,27 . Whereas THz and MIR pulses have unveiled excitonic correlations in quantum wells 26 , perovskites 27 , and monolayer TMDs 19,20 , excitons in TMD hetero-bilayers have not been resolved.…”
mentioning
confidence: 99%
“…S2b,c) is transmitted through the sample. The interaction with the photoinjected e-h pairs imparts a characteristic change on the amplitude and the phase of the MIR waveform, which we directly record by electro-optic sampling 19,20,[25][26][27][28] . A Fourier transform and a Fresnel analysis allow us to extract the full dielectric response of the non-equilibrium system 25,26 (see Methods).…”
mentioning
confidence: 99%
“…Nanocrystalline versions of these materials also exhibit long carrier lifetimes, tunable emission energies over the entire visible spectrum, and high quantum yields. This has led to further research into their photoluminescence properties, as well as their use in light‐emitting devices and low‐threshold lasers …”
Section: Introductionmentioning
confidence: 99%
“…[5] Nanocrystalline versions of these materials also exhibit long carrier lifetimes, tunable emission energies over the entire visible spectrum, and high quantum yields. This has led to further research into their photoluminescence properties, [6][7][8][9][10] as well as their use in light-emitting devices [11] and low-threshold lasers. [12][13][14][15] Despite these wonderful properties, lead is a toxic heavy metal that is detrimental to the nervous and reproductive systems of humans and also raises concerns over environmental compatibility.…”
Section: Introductionmentioning
confidence: 99%